DESKRIPSI HASIL PENGGUNAAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E – LKPD) BERBASIS QUIZIZZ PADA MATERI BARISAN DAN DERET ARITMATIKA DI KELAS X SMK NEGERI 1 BULANGO SELATAN - Evi Hulukati; Hindriani Tuna; Auli Irfah (PHI: Jurnal Pendidikan Matematika, 2026)
This study is part of a broader (umbrella) research project conducted by three researchers, consisting of development, experimental, and descriptive studies. This tudy aims to describe the results of implementing a Quizizz-based Electronic Student Worksheet (E-LKPD) on the topic of arithmetic sequences and series in Grade X at Vocational High School State 1 Bulango Selatan. The research employed a quantitative descriptive method. The population consisted of all Grade X students of Vocational High School State 1 Bulango Selatan in the 2023/2024 academic year, comprising four classes with a total of 87 students. The sample was selected using Cluster Random Sampling through a lottery method among the four classes, and Class X ASKEP A was chosen as the sample. The findings indicate that the use of the Quizizz-based E-LKPD received a positive response from students. This is reflected in the student response questionnaire results, which reached 94.5%, indicating that most students felt assisted in understanding arithmetic sequences and series, and were more motivated and engaged during the mathematics learning process. Therefore, this media can serve as an innovative alternative for implementing digital-based learning in schools.